2010
DOI: 10.1116/1.3425805
|View full text |Cite
|
Sign up to set email alerts
|

Growth of epitaxial iron nitride ultrathin film on zinc-blende gallium nitride

Abstract: The authors report the growth of iron nitride on zinc-blende gallium nitride using molecular beam epitaxy. First, zinc-blende GaN is grown on a magnesium oxide substrate having ͑001͒ orientation; second, an ultrathin layer of FeN is grown on top of the GaN layer. In situ reflection high-energy electron diffraction is used to monitor the surface during growth, and a well-defined epitaxial relationship is observed. Cross-sectional transmission electron microscopy is used to reveal the epitaxial continuity at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…This peak can be assigned to FeN(111) and the LP comes out to be 4.45Å. Generally, the LP of FeN films has been found anywhere between 4.3 to 4.55Å and when FeN films are deposited at low T s (< 400 K), LP ≈ 4.5Å [32,34,75] and at high T s , LP reduces to about 4.3Å [47,75]. Therefore, from our XRD measurements, we can confirm the formation of mononitride FeN phase.…”
Section: Structural and Magnetic Characterization Of Fen Thin Filmmentioning
confidence: 93%
See 2 more Smart Citations
“…This peak can be assigned to FeN(111) and the LP comes out to be 4.45Å. Generally, the LP of FeN films has been found anywhere between 4.3 to 4.55Å and when FeN films are deposited at low T s (< 400 K), LP ≈ 4.5Å [32,34,75] and at high T s , LP reduces to about 4.3Å [47,75]. Therefore, from our XRD measurements, we can confirm the formation of mononitride FeN phase.…”
Section: Structural and Magnetic Characterization Of Fen Thin Filmmentioning
confidence: 93%
“…FeN compounds were extensively studied by Schaff et al [23][24][25][26] in late 1990s. Subsequently, FeN thin films were synthesized using ion beam sputtering [27], dc/rf magnetron sputtering [28][29][30][31][32][33][34][35][36][37][38], pulsed laser deposition (PLD) [39][40][41][42], high power impulse magnetron sputtering [43], nitrogen plasma assisted molecular beam epitaxy (MBE) [44][45][46][47][48] and very recently under HPHT [12,16,[49][50][51]. From applications points of view, the mononitride FeN is also very interesting as its oxidation resistance makes it a effective catalyst in chemical reactions [52,53], it can be used as a precursor to yield magnetic phases in a controlled way [38,44,54,55] and also in biomedical applications [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From recent experimental works, it can be observed that FeN crystalizes in the ZB-type structure only (under ambient pressure and temperature) and the existence of the RS-type FeN has been questioned in several recent works [34][35][36]. Though theoretical works predict both ZBand RS-type structures for FeN and CoN, but under ambient temperature and pressure, the ZB-type structure is preferred [21].…”
Section: Introductionmentioning
confidence: 99%
“…Among the late TMMN, FeN is the most studied compound yet its structural and magnetic ground state is still debated [25,26]. From recent experimental works, it can be observed that FeN crystalizes in the ZB-type structure only (under ambient pressure and temperature) and the existence of the RS-type FeN has been questioned in several works [27][28][29]. Though theoretical works predict both ZB and RS-type structures for FeN and CoN but under ambient temperature and pressure, the ZB-type structure is preferred [21].…”
Section: Introductionmentioning
confidence: 99%